IMPLEMENTASI PROGRAM PELATIHAN LITERASI KEUANGAN BERBASIS TEKNOLOGI DIGITAL PADA PROGRAM PENDIDIKAN KESETARAAN PAKET C DI PKBM ASH-SHODDIQ - Masdian Nurhadi; Enceng Mulyana; Sri Nurhayati; Cucu Sukmana (Jurnal Visi Ilmu Pendidikan)
Equipping soft skills to teach citizens to master digital-based financial management through digital-based financial literacy is an important strategy in improving equity education. This study aims to clearly describe how PKBM Ash-Shoddiq Lembang West Bandung Regency implements digital-based financial literacy training. In this study, descriptive method was used to obtain qualitative data from 10 respondents consisting of 5 academic residents, 3 teaching assistants, and 2 managers. The results showed that the implementation of digital-based financial literacy training began with the planning, socialization, and needs identification stages, followed by implementation using andragogical and participatory strategies using Microsoft Excel media. The results of the training showed an increase in understanding and knowledge in the main aspects of financial literacy.